STRATEGI PEMENANGAN HASRIZAL DARI PARTAI AMANAT NASIONAL (PAN) DALAM PEMILIHAN LEGISLATIF KOTA DUMAI TAHUN 2019 - Amalina, Wadiah; ', Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Strategy for winning legislative candidates in the 2019 Dumai City legislative election. In the 2019 Legislative Election, Hasrizal experienced an increase in votes from 1,282 to 2,444 votes from the 2014 Legislative Election. The increase in votes obtained by Hasrizal in the 2019 Legislative Election is an achievement and interesting to know related to the strategy used by Hasrizal so that he was able to gain vote support from the community. This research aims to determine Hasrizal's winning strategy from the National Mandate Party (PAN) in the 2019 Dumai City Legislative Election. The research approach used is qualitative with descriptive research type. The research location is in Dumai City. Data collection techniques use interview and documentation techniques. Data analysis techniques using qualitative analysis techniques. Researchers use Peter Schorder's (2022) theory regarding political strategy, namely offensive strategy and defensive strategy. The research results show that the offensive strategy used by Hasrizal is to expand the voter network through regional organizations. The offensive strategy penetrates voters by strengthening relations with workers/employees, as well as approaching the community through coaching programs and exploring the potential of administrators and sympathizers through party organizations. The defensive strategy to retain voters is to maintain their constituents and electoral areas through friendship and development programs. The defensive strategy used to close voters is to close their electoral areas from political opponents through outreach to the community and distribution of calendars, stickers and business cards. Kata Kunci : Strategi Politik, Pemilihan Legislatif, Calon Legislatif